(untitled) (Journal of Patan Academy of Health Sciences, 2023)
Introduction: The COVID-19 pandemic first detected in December 2019 has claimed so many lives globally as well as in Nepal. Inflammatory changes in SARS-CoV-2 infection can lead to anemia. This study aims to find the prevalence of anemia and mortality among anemic patients in COVID patients admitted to a tertiary care centre in Nepal. Method: A descriptive cross-sectional study with data collected retrospectively between May 2021 to February 2022 on patients with proven COVID-19 admitted to Patan Hospital. Result: Among 890, anemia was prevalent in 296(33.25%) (CI 95%, 30.17-36.35) patients which was more among the female population. The mean hemoglobin was 10.68±1.62 g/dl in anemic patients. Mild anemia was present in 215(72.6%) patients followed by moderate in 64(21.6%) patients and severe in 17(5.8%) patients. The mortality in anemic patients was 43(14.5%). Conclusion: One third of COVID-19 patients admitted to Patan Hospital had anemia which was found to be similar to studies done in similar setting. One in four COVID-19 patients with anemia had died was found to be lower than other studies done in similar settings.